Major transitions in the history of life - Blackstone, Neil (Henry Stewart Talks, 2016)
The origin of life, Major transitions and size increase, Formation of cells, Molecules in the cellular environment, Complex cells, Conflict mediation, Multi level selection, Multicellularity, Origin of societies